STUNTING PADA BALITA DIPENGARUHI KESEHATAN GIGI GELIGINYA - Munifah Abdat (Journal of Syiah Kuala Dentistry Society, 2019)
The target of Global Nutrition in 2025 is to reduce the prevalence of stunting. In 2018 the prevalenceof stunting and severely stunted in Indonesia decreased to 30.8% and Aceh became the 3rd highestprovince. Stunting is a condition when a child's height is shorter than other children his age. This iscaused by one condition where a person experiences chronic nutritional deficiencies since the child isin the mother's womb and in the early period after the child is born, begins to appear when the child is2 years old. Factors causing and supporting the occurrence of stunting in toddlers include unbalancedfood intake, LBW and illnesses suffered due to infection. The incidence of infection can be associated with the occurrence of dental caries that often occurs in toddlers and lasts longer. As a result of dentalcaries certainly causes pain in the respondent, which in turn will disrupt the function of masticationand affect the nutritional status. If the nutritional status is disturbed, you are at risk of stunting.Nutritional deficiencies that were chronic in stunting toddlers have an impact on the growth of bonesand teeth, so that stunted toddlers experience delays in tooth eruption. Conclusion. Stunted toddler isnot only caused by a lack of balanced nutritional intake but can also be affected by the condition of theteeth of toddlers who have caries and can interfere with the process of masticating food.Keywords: Stunting in Toddlers, Dental Caries